DOES AUDIT QUALITY SHAPE FINANCIAL OUTCOMES? EXAMINING BOARD INDEPENDENCEASASTRATEGICMODERATORFORENHANCEPERFORMANCE OF DEPOSIT MONEY BANKS IN AN EMERGING ECONOMY - Emmanuel Imuede Oyasor (Gusau Journal of Accounting and Finance)
This study examines the influence of audit quality and board independence on the financial performance of Nigerian banks from 2014 to 2023, using panel data and generalized least squares (GLS) random effects regression models. While neither audit quality nor board independence individually demonstrated significant direct effects on return on equity (ROE), firm size exhibited a positive and statistically significant impact on performance. Additionally, the moderating role of board independence on the audit quality–performance nexus was not supported by the empirical evidence. These findings suggest that the governance mechanisms studied interact in complex ways within Nigeria‘s unique institutional context. The study contributes to corporate governance literature by highlighting the limitations of conventional governance assumptions in emerging marketsandunderscorestheimportanceofcontextualfactors.Policyimplicationsincludetheneedforenhanced audit quality metrics and strengthened board independence mechanisms tailored to local realities. Recommendations for future research focus on richer audit quality proxies and broader sectoral analyses.